Pattern reconfigurable printed Yagi-Uda antenna - Kittiyanpunya, Chainarong; Krairiksh, Monai (My University, 2015)
This paper presents a pattern reconfigurable antenna which is based on Yagi-Uda dipole antenna. The antenna can operate at ISM band of 2.45 GHz. It consists of microstrip-to-coplanar stripline (CPS) transition, driven elements and parasitic elements. The switch of driven element can be controlled by using PIN diodes while parasitic element function can be either reflector or director with different PIN diode states. The maximum of radiation patterns are in azimuth plane with four directions around the antenna to the directions of O = 40°, 120°, 220° and 320°.
Keywords: beam switching; microstrip-to-CPS transition; pattern reconfigurable antenna; Yagi-Uda antenna